Identifying areas and centers of endemism in the Gran Chaco with Fabaceae as a diversity indicator - Morales, Matias; Bagnatori Sartori, Angela Lucia; Prado, Darién Eros; Fortunato, Renée Hersilia (Springer Nature, 2025)
The Gran Chaco ecoregion is the second largest forest in South America and exhibits the highest deforestation rate in the world, threatened by the expansion of agriculture, lodging and cattle grazing. The Chacoan endemism richness has still been not adequately investigated. In this work, we detected areas of endemism (AEs) and centers of endemism (CEs) using Fabaceae as a proxy, with a novel combination of analyses to explore the endemism distribution pattern of Chacoan plants: NDM-VNDM analyses to detect AEs, and endemic indexes and clustering to detect CEs. We recovered regions with high concentration of endemic and highly restricted taxa: (1) Sierra Chaco; (2) Sierra/ Arid Chaco ecotone; (3) the interior Dry Chaco; (4) the upper Paraguay River Basin; and (5) the Low Paraguay–Paraná River Basins. We also determined which taxa contributed to configure the AEs and CEs, the environmental variables explaining their potential distribution, the ecological niche overlap and preferences of habitat between them. Dry Interior Chaco and the Dry/Sierra Chaco ecotone included taxa sharing similar and highly overlapped niches. The remainder, located in Humid and Sierra Chaco, showed restricted and variably overlapped ecological niches, suggesting a complexity of habitats requiring further intensive sampling for conservation measures. Unweighted Pair Group Method with Arithmetic Mean (UPGMA) also recovered grouping patterns contributing to improve the regionalization of the Gran Chaco based on the exclusive species of its biota. These areas are potential biodiversity hotspots and speciation centers for the native flora in subtropical South America and can serve as tools for conservation policies, especially in Sierra Chaco and Dry Chaco.